Evaluation of Landslide Possibility Based on Pore Water Pressure Mechanism and Mitigation - Namdar, Abdoullah (2012)
In this investigation more than 200 papers have been evaluated for mitigation of natural hazard, it is important issue in human life. The landslide repeated periodically in the world due to several reasons. The site geological, geotechnical and geomorphological characteristics along with force nature and surcharge are playing important role in pore water pressure mechanism which is one of the main factors in landslide. This is a study for better understanding landslide phenomenon. Author made an attempt by using shaking table test result for explaining pore water pressure mechanism in saturated sandy subsoil affected by liquefaction. The embankment-subsoil model is helped to simulate pore water pressure in landslide. The investigation is analyzed pore water pressure in experimental, and provides appropriate guidance for landslide failure prediction. It is recommended for research priorities in next generation of research. These included i) Analysis of pore water pressure in generating landslide. ii) Identify liquefiable layer and zone, and liquefaction magnitude movement for realize landslide zone and slope stability assessment. iii) Mitigation technique for landslide to understand slope potential failure.